Smartphone-Based Early Child Dection To Monitor Children's Growth And Development - Kirana, Sasi; Pristianto, Arif; Dewangga, Mahendra Wahyu; Khairuddin, Gumilang Wahyu (P3M Universitas 'Aisyiyah Surakarta, 2024)
Background: Communication technologies, especially smartphones, offer great potential in improving health education by providing easily accessible information. Provide knowledge and understanding as well as attention to the child's developmental conditions, namely the physical and motor conditions that exist within the individual to avoid and overcome the occurrence of disorders. Methods: This type of research uses Research and Development (R&D) research and development methods. To produce certain products, research is used in the nature of needs analysis and to test the effectiveness of the product so that it can function in the wider community, research is needed to test the effectiveness of the product. Results: These test results are important for further improvements and for future research. Users say that this application is very helpful in monitoring children's growth and development and can be accessed at any time. Conclusion: This application about child growth and development is quite suitable for use. although it still requires further improvements and development so that the application is better used in the future.